FLEXIBLE, WIRELESS, INDUCTIVELY COUPLED SURFACE COIL RESONATOR FOR EPR TOOTH DOSIMETRY. Issue 1 (23rd December 2016) - Schreiber, Wilson; Petryakov, Sergey V.; Kmiec, Maciej M.; Feldman, Matthew A.; Meaney, Paul M.; Wood, Victoria A.; Boyle, Holly K.; Flood, Ann Barry; Williams, Benjamin B.; Swartz, Harold M.
Abstract: Managing radiation injuries following a catastrophic event where large numbers of people may have been exposed to life-threatening doses of ionizing radiation relies on the availability of biodosimetry to assess whether individuals need to be triaged for care. Electron Paramagnetic Resonance (EPR) tooth dosimetry is a viable method to accurately estimate the amount of ionizing radiation to which an individual has been exposed. In the intended measurement conditions and scenario, it is essential that the measurement process be fast, straightforward and provides meaningful and accurate dose estimations for individuals in the expected measurement conditions. The sensing component of a conventional L-band EPR spectrometer used for tooth dosimetry typically consists of a surface coil resonator that is rigidly, physically attached to the coupler. This design can result in cumbersome operation, limitations in teeth geometries that may be measured and hinder the overall utility of the dosimeter. A novel surface coil resonator has been developed for the currently existing L-band (1.15 GHz) EPR tooth dosimeter for the intended use as a point of care device by minimally trained operators. This resonator development provides further utility to the dosimeter, and increases the usability of the dosimeter by non-expert operators in the intended use scenario.